Whole-genome sequencing of Chlamydia trachomatis isolates from persistently infected patients. (April 2022) - Pitt, Rachel; Doyle, Ronan; Theilgaard Christiansen, Mette; Horner, Paddy; Hathorn, Emma; Alexander, Sarah; Woodford, Neil; Cole, Michelle; Breuer, Judith
Background: Current understanding of the causes of treatment failure in Chlamydia trachomatis is poor and antimicrobial susceptibility data are lacking. We used genome sequencing to seek evidence of antimicrobial resistance in isolates sourced from patients who were persistently infected. Methods: Genomic DNA was extracted from C. trachomatis isolates cultured in McCoy cell monolayers. Sequencing libraries were prepared using the SureSelect XT Illumina paired-end protocol. Paired reads were mapped against a reference genome and single nucleotide variants (SNVs) were identified. Results: Seven isolates from persistently infected patients and five isolates from successfully treated patients were sequenced. No previously reported SNVs associated with antimicrobial resistance were found. A unique SNV was identified in the gyrA gene of one treatment failure isolate but was located outside of the quinolone resistance determining region; this SNV has been previously reported in other members of the Chlamydiaceae family. Conclusion: No genomic evidence was found to explain the differences in clinical outcome for our two groups of patients. A mutation unrelated to antimicrobial susceptibility was found in an isolate from a persistently infected patient. The cause of these persistent infections with C. trachomatis remains unclear.